The determinants of mobile subscriber retention in Sweden - Srinuan, Pratompong; Bohlin, Erik; Madden, Gary (Routledge, 2012)
A binomial logit model is estimated on individual telecommunications service use data. The model examines whether operator-specific switching costs and termination-based prices impact on retention. The results show that service attributes (brand image and on-net prices) are significant in retaining subscribers. As customers of larger networks face higher switching costs, only the largest operator can use termination-based pricing to retain mobile subscribers.